Efektivitas Pembuatan Lubang Tanam di Perkebunan Kelapa Sawit dengan Quality Control Circle - Yudhi Pramudya -; Yeremia Pandiangan; Galuh Banowati; Sukarji (Jurnal Pengelolaan Perkebunan (JPP), 2023)
The study investigates the effectiveness of planting hole creation in oil palm plantations using the Quality Control Circle (QCC). Field observations were conducted to measure the hole-digging tool's diameter and depth before and after modification. Results showed that the modified tool is more effective than the old tool, requiring only 13 seconds per polybag to create holes. The T-PLANT tool produced uniform holes with optimal depth, resulting in improved productivity, reduced costs, and improved work quality. Implementing QCC with this modified tool can enhance the effectiveness of planting hole creation, improve productivity, reduce costs, and improve work quality in oil palm plantations.